Depósitos de caulino associados à faixa metamórfica de Espinho–Albergaria-a-Velha (NW de Portugal) : quadro geológico estrutural e morfotectónico : structural geology and morphotectonics framework
This work synthesizes the present knowledge of the main occurrences of the kaolin deposits located near the NW of Portugal and Galicia Atlantic shoreline, namely throughout the Espinho-Albergariaa- Velha metamorphic belt. A geodynamic insight of the geotectonic and morphostructural control of the several outcropping kaolin deposits is presented in order to establish possible exploration guidelines of the georesources. The observation of a geological resources map of the Iberian Peninsula testifies that kaolin deposits exist all over the territory. Nevertheless, one may conclude that along the NW Iberia this geological resource is well located, being fitted with major tectonic lineaments. The genesis of these deposits is dependent on several constraints, namely lithology, tectonics and morphology. A multidisciplinary approach was applied to the systematization of residual kaolin deposits located on the South of Porto city, as well on the vicinities of Aveiro region. (…)This way, we may conclude that the association of the geotectonical, geomorphological, mineralogical and palaeoenvironmental factors were responsible for the kaolin deposits formation, in a first stage by a hydrothermal action and afterwards through a continuous alteration originated by the action of meteoric geofluids.